Extracellular transmission of a DNA mycovirus and its use as a natural fungicide - Yu, Xiao; Li, Bo; Fu, Yanping; Xie, Jiatao; Cheng, Jiasen; Ghabrial, Said A.; Li, Guoqing; Yi, Xianhong; Jiang, Daohong (Proceedings of the National Academy of Sciences - PNAS, 2013)
Mycoviruses are thought not to be infectious as free particles and to lack an extracellular phase in their life cycles, limiting the broad use of hypovirulence-associated mycoviruses in controlling fungal disease. Here, we demonstrate that purified particles of a DNA mycovirus, Sclerotinia sclerotiorum hypovirulence-associated DNA virus 1 (SsHADV-1), are infectious when applied extracellularly to its host Sclerotinia sclerotiorum . Virus particles isolated from an infected host can infect the hyphae of virus-free S. sclerotiorum directly when applied to hyphae grown on potato dextrose agar or sprayed on leaves of Arabidopsis thaliana and Brassica napus , regardless of vegetative compatibility affiliation. When applied to leaves, the virus can suppress the development of lesions. SsHADV-1 can also reduce disease severity and enhance rapeseed yield significantly under field conditions. SsHADV-1 has a narrow host range; it can infect Sclerotinia minor and Sclerotinia nivalis , sister species of S. sclerotiorum , and cause debilitation of these two fungi, but cannot infect or transfect other tested fungi, such as Botrytis cinerea , which shares the same family with S. sclerotiorum . Virus particles are likely to be very stable on the leaves of A. thaliana plants because viral DNA could be detected at 15 d postinoculation on unwounded leaves and at 10 d postinoculation on wounded leaves, respectively; however, this virus could not infect and move in plant cells. Our findings may prompt a reconsideration of the generalization that mycoviruses lack an extracellular phase in their life cycles and stimulate the search for other DNA mycoviruses with potential use as natural fungicides.